PENINGKATAN PRODUKTIVITAS DAN MUTU KRIPIK SINGKONG DI KABUPATEN PROBOLINGGO - Sadar Wahjudi; Bambang Soepeno; Krispitono Krispitono (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2017)
Mom housewife Hamlet II North Village Sambirampak Kidul District Kotaanyar and Krajan Sumber Rejo District of Paiton Probolinggo in improving its economy by making the effort to make cassava chips, the cutting process cassava are still using manual so that the slaughtering is not the same / uniform and processes running slow it greatly affects the competitiveness of products to other regions / cities as well as difficult to meet the growing market demand. In addition to wrapping / packaging did not pay attention to material packaging (plastic), as well as the density of packing can lead to life-time of his very short (the survey only 1 week) and estitika of packaging its themselves are less interesting as well as harmful to health. With cassava chopper machine and a table for wrapping, making cassava cutting more efficient, effective productivity into 4 x more than the manual way and the life time of cassava itself longer 3 months compared with manual stripping. Besides better production performance and attractive than ever before are using copy paper wrapper incorporated herein.